DIAGNOSIS KEBUNTINGAN DINI PADA KAMBING KACANG (Capra sp.) MENGGUNAKAN ULTRASONOGRAFI TRANSKUTANEUS (Early Pregnancy Diagnosis in Dwarf Goat (Capra sp.) by Transcutaneous Ultrasonography) - Arman Sayuti; Juli Melia; Ira Khubairoh Marpaung; Tongku Nizwan Siregar; Syafruddin S; Amiruddin A; Budianto Panjaitan (Jurnal Kedokteran Hewan, 2016)
This research aimed to determine the optimum time for early pregnancy diagnosis in dwarf goat by trancutaneous ultrasonography and to determine ultrasonography imaging of dwarf goat pregnancy since insemination until embryo formation. Animal used in this research were 3 productive female goats with normal estrus cycle and 1male goat. The female goats were kept in separation pen from the male goat. The grasses were fed three times a day and additional feed were fed in the morning and afternoon with the water was given ad libitum. The goats were synchronized with intramuscular double injection of 1 ml estron®/each female goat with 11 days interval. The observation of estrus was examined using male goat following the second injection of estron®. The sign of estrus in female goats were characterized with standing immobile and allow the male goat to mount them. If the signs had been evident, the female goats were naturally mated. Pregnancy was determined by the presence of the embryonic vesicle by isoechogenic until hyperechogenic visualization surrounded by hypoechogenic of the embryonic fluid. The result of the transcutaneous ultrasonography in dwarf goat pregnancy showed the presence of embryonic vesicle on day 14 and embryo with isoechogenic visualization was detected on day 24 of pregnancy.Key words: dwarf goat, early pregnancy, transcutaneous ultrasonography